Hilary Putnam and the Nostalgia of Pragmatism - Faerna, Ángel (Analysis. Journal of Philosophical Research, 2018)
The aim of this paper is to offer a brief survey of the relationship between HilaryPutnam and pragmatism. In the first and second sections I comment on Putnam’sphilosophical shift from “orthodox” analytic philosophy to “neopragmatism”, and takea look at his controversy with Richard Rorty concerning the meaning of pragmatism.The third section points at Putnam’s and Rorty’s rejection of the Peircean definition oftruth as a key issue to account for the differences between neopragmatist philosophersand classic pragmatists (including Dewey). The final section draws some conclusionsfrom the previous discussion concerning the “narrative” of contemporary pragmatism.